JAVANESE WOMAN IN NOVEL AROMA KARSA BY DEE LESTARI - Tiara Ayu Meutia; Nuril Hidayati (Program Studi Bahasa Inggris, Universitas Panca Marga, 2023)
This research analyzed the representation of Javanese woman in Aroma Karsa novel by Dee Lestari. The aim of this study is to know the representamen meaning and describe the representation of Javanese woman in Aroma Karsa novel. The research is uses semiotic theory based on Charles Sanders Peirce’s semiotic model: representamen, object, interpretant. Aroma Karsa novel tells Javanese woman as strong, brave, smart, and idealistic. This research hopes to be used as a useful contribution to the implementation of feminism and changing the society’s perspective on Javanese woman who are considered as weak and dependent on men.